Enzymatic activity of alginate coated and pulsed light treated fresh-cut cantaloupes (Cucumis melo L. var. reticulatus cv. Glamour) during chilled storage - Koh, Pei Chen; Mohd Adzahan, Noranizan; Karim, Roselina; Zainal Abedin, Nur Hanani; Rosli, Siti Zaharah; Hambali, Nor Hasni (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The objective of the present work was to investigate the effects of alginate coating combined with repetitive pulsed light (RPL) treatment on the enzymatic activity of fresh-cut cantaloupes during chilled storage. Fresh-cut cantaloupes were coated with alginate (1.86%, w/v) followed by RPL treatment (0.9 J/cm2 at every 48 h up to 26 d) during storage. Untreated samples and samples with alginate or RPL alone were used as controls. Enzymatic activities [polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL), peroxidase (POD), pectinesterase (PE), polygalacturonase (PG), pectate lyase (PEL), β-galactosidase (β-Gal), α-arabinofuranosidase (α-AF) and cellulase] of fresh-cut cantaloupes were evaluated every 4 d during storage. Neither alginate coating nor RPL treatment has any effect on the activities of PE and PEL of fresh-cut cantaloupes during storage. The individual treatment or in combination did not increase the PAL, PPO, PG and cellulase activities of fresh-cut cantaloupes throughout the storage. Alginate coating with or without RPL was effective in maintaining low POD activity of fresh-cut cantaloupes. In addition, treatments using alginate coating or alginate coating+RPL were effective in reducing the β-Gal and α-AF activities of fresh-cut cantaloupes during storage. Overall, alginate without or with RPL was effective in reducing changes of enzymatic activities in fresh-cut cantaloupes during storage.